2018
DOI: 10.5543/khd.2018.19870
|View full text |Cite
|
Sign up to set email alerts
|

Kalp Kapak Protezleri Sonrası Antikoagülan Tedaviye Uyum

Abstract: Kalp kapak hastalıkları oldukça yaygın görülen sağlık sorunlarından biridir. İleri derece kapak hastalıklarında cerrahi tedavi ön plana çıkmaktadır. Kalp kapak ameliyatları sonrasında hasta hem ameliyat hem de antikoagülan ilaç nedeniyle uyum sağlamak durumundadır. Cerrahi yara, sternotomi, kardiyak rehabilitasyonun yanında antikoagülan tedavinin başlanması, sürdürülmesi ve komplikasyonların önlenmesinde uyum oldukça önemlidir. Beklenen yaşam süresinin artması ve mekanik protez takılma sınırının 60 yaşa kadar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It is a priority to provide and maintain a consultancy service evaluating individual habits and examining the factors leading to nonadherence in addition to the drug dose. It is reported that if the patients are poorly educated they discontinue anticoagulants depending on the educational level of populations and develop serious complications [ 5 , 6 ].…”
mentioning
confidence: 99%
“…It is a priority to provide and maintain a consultancy service evaluating individual habits and examining the factors leading to nonadherence in addition to the drug dose. It is reported that if the patients are poorly educated they discontinue anticoagulants depending on the educational level of populations and develop serious complications [ 5 , 6 ].…”
mentioning
confidence: 99%